THE POET AND NATURE: CHRONOTOPE TARAS SHEVCHENKO IN THE ART OF ODESA 1960s. European context - ТАРАСЕНКО, А. А.; ТАРАСЕНКО, О. А.; СІКОРСЬКА, В. Ю. (Art and Design, 2023)
The purpose of the article is to study the image of Taras Shevchenko in the art of Odesa in the 1960s. The topic is considered in the context of the poetics of European romanticism: “The poet and nature". Historical-cultural, comparative, iconographic, iconological, and hermeneutic methods are used. Based on the study of the content in terms of ideas, iconography, and style of Shevchenko’s image in the paintings of M. Bozhiy, A. Atsmanchuk, and K. Filatov, it is shown in the sculpture that the nature of the interpretation of Kobzar’s image is related to the time and place of creation of works of fine art. The beginning of the Space Age, that coincided with the anniversaries of the poet’s death (1861) and the poet’s birth (1814), which were celebrated in 1961 and 1964, respectively, expanded the perception of Shevchenko’s personality in space and time. On the basis of the created typological series, it was revealed that the iconography of the path and the image of the inspired poet in the composition of Bozhiy is related to the image of Beethoven and Hugo in the art of Germany and France. The syncretism of the metaphor of the winged poet in poetry, painting and sculpture was revealed. The lyrical dominant of Shevchenko’s image in the creativity of Odesa artists of the 1960s is revealed. It was clarified that the work on the plein air in parallel with the creation of the picture form in the workshop made it possible to achieve the unity of the colorful matter in the image of Kobzar and the elements of creation. The scientific novelty of the publication lies in the fact that it shows for the first time that the place and historical time of the creation of the artistic image of Kobzar –the chronotope – is reflected in the visual art of Odesa. The interrelationship of the system of poetic and pictorial images of M. Bozhiy’s painting "My thoughts, my thoughts..." with Shevchenko’s poetry is studied. It is clarified that the supernatural (metaphysical) state of Shevchenko’s poetic inspiration is expressed through the portrait and the natural environment of the panoramic landscape of his native land. The role of the Odesa landscape school in the creation of Kobzar’s lyrical image is investigated. The relationship between the picture-panel and the sculptural monument is considered. The presented materials, their artistic and stylistic analysis and generalization can be used in scientific studies dedicated to the image of T. Shevchenko in visual arts and literature.